Efficacy, safety and pharmacokinetics of ilaprazole infusion in healthy subjects and patients with esomeprazole as positive control - Wang, Hongyun; Shao, Feng; Liu, Xuemei; Xu, Wen; Ou, Ning; Qin, Xianghong; Liu, Fang; Hou, Xuemei; Hu, Haitang; Jiang, Ji (British journal of clinical pharmacology, 2019)
Aims The objectives were to investigate the pharmacokinetics, pharmacodynamics and safety of ilaprazole infusion in healthy subjects and patients with esomeprazole as positive control, and then recommend the dosage regimen for Phase 2b/3 studies. Methods Three clinical studies were performed. First, 16 healthy subjects received infusion of ilaprazole 30 mg or esomeprazole 80 mg. Second, 12 healthy subjects received ilaprazole 20 mg followed by 10 mg once daily for 2 days. Finally, 20 patients with duodenal ulcers received ilaprazole 20 mg followed by 10 mg for 2 days or esomeprazole 40 mg twice daily for 3 days. Serial blood samples were collected and intragastric pH was recorded. Results The mean percentages time of intragastric pH >6 was 63.6 and 51.7% for healthy subjects after receiving ilaprazole 30 mg and esomeprazole 80 mg. Linear pharmacokinetics was observed when the dose was increased to 30 mg but the effect was saturated. Ilaprazole 20 mg followed by 10 mg for 2 days provided higher plasma exposure in healthy subjects than patients, but the effect was comparable. After multiple administrations, ilaprazole provided similar effect to esomeprazole. Ilaprazole infusion was safe and well tolerated without serious adverse events. Conclusions Ilaprazole provided comparable effect of pH control to esomeprazole, with lower dose and fewer times of administration. There was no significant difference of ilaprazole between healthy subjects and patients regarding intragastric acid inhibition. A loading dose of ilaprazole 20 mg followed by 10 mg once daily for 2 days was recommended for Phase 2b/3 studies.